From Conflict Zones to Europe: Syrian and Afghan Refugees’ Journeys, Stories, and Strategies - Belabbas, Souhila (2022)
This article explores the journeys of Syrian and Afghan refugees to Europe, looking at two of the largest and politically most salient flows of asylum seekers during the 2010s. Following political disturbances in their home countries, millions of Syrians and Afghans have been forcibly displaced or had to seek safety elsewhere. In search of protection for themselves and their families, some of them had to cross multiple borders to reach European destinations or hope to be resettled there. This article looks at the factors that shape the journeys of asylum seekers and the uncertain features of the process of moving from one unexpected location to another, with an emphasis on the overlapping role of information, social networks, resources, and pure chance. Our aim is to locate the refugee journeys in the context of significant social institutions that may determine their decisions, migratory trajectories, and consequently their entire journeys. The present research involves in‐depth qualitative interviews. Drawing on an ethnographic approach and a multi‐sited methodology, we bring together diverse refugee voices and narratives and focus on the role of information in their mobility. The results help us verify assumptions about different aspects of migrant journeys, mechanisms involved in the decision‐making of the actors involved, the role of networks (or networking) and information exchange, and other relevant aspects expounded throughout the article. Our findings suggest that social networks, family status, age, disability, human, social, and cultural capital, their intersections, and, in the end, chance, play an important role in the shaping of the asylum seekers’ migration trajectories.